Zaštita na radu medicinskih sestara/tehničara zaposlenih u zoni ionizirajućeg zračenja - Barukčić, Dragana; Nola, Iskra Alexandra (2021)
Radiation is the energy that travels through space and is present everywhere around us. Life on earth evolved in an environment of ionizing radiation. The discovery of ionizing radiation marks the beginning of a significant period in medical diagnosis and treatment. The discovery of X-rays and their use in medicine prompted a growing awareness of their adverse effects on the human body. Increased use of ionizing radiation increases the likelihood of harmful health hazards if it is not used properly. In healthcare settings, ionizing radiation is used in diagnostic and interventional radiology, nuclear medicine and oncology. Ongoing development of medical radiology brings new insights related to diagnosis and treatment, and thus to the refinement of certain procedures. Nurses/technicians exposed to ionizing radiation on a daily or occasional basis during their work may reduce the risk of undesired radiation exposure with adequate occupational safety measures that will prevent unnecessary exposure to high doses. The paper aims to review and contribute to the preservation and protection of the health of nurses/ technicians exposed to ionizing radiation sources and their safe work. Prevention, education, and ionizing radiation protection measures to be taken to reduce exposure are presented, including adverse effects on human health. Exposure to ionizing radiation has been shown to be harmful and its effects are mutagenic, teratogenic and carcinogenic. These effects can occur in different forms and in different time spans. Nurses/technicians' exposure to ionizing radiation is associated with a number of health risks. In order to reduce the negative effects, a good professional education is needed as a first prerequisite for protection. It involves thorough knowledge of the consequences of radiation, and of all means and methods for reducing radiation exposure.
Bibliografija: str. 61-62.
Sažetak ; Summary.
Keywords: Medicinski djelatnici -- Ionizirajuće zračenje -- Zaštita na radu